Konsep Dasar Islam Wasathiyah Perspektif Ulama Muslim - Siti Solichatun Zakiah; Mukh Nursikin (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The religion of Islam has given blessings to all people and instructs in every good for humans and one another. Every teaching contained in Islam relies on the Qur'an and the Sunnah of the Messenger besides that some other human beings also agree to believe in ijma', qiyah for the source of learning Islam. Regarding wasathiyah Islam, it does not mean not giving explanations or not giving firmness to something like a neutral attitude on a particular subject, nor a middle attitude as described by Greek philosopher thinkers. Unlike what is introduced in the term wasath which is (middle), where it gives direction that wasathiyah does not force humans to achieve something good and appropriate, for example, knowledge, wealth, worship, and others. This article explains the concept of wasathiyah Islam from various thoughts of the figures and aims to find out the concept of wasathiyah in Islam and to find out how the figures view the concept of wasathiyah in Islam. The concept of wasathiyah Islam is very important to be studied to limit the movement of the Islamic caliph.